Identidade das crianças quilombolas na Comunidade de Bela Aurora no Nordeste do Pará - MATOS, Damaris da Silva (2022)
This study analyzes the identity of quilombola children in the community of Bela Aurora in Northeastern of Pará. The quilombola childhoods are experienced by historical and sociocultural practices, related to the preservation of memory, festivities, and religiosity in which the children participate in their territory because they have conquered rights and have increasingly shown that the child is also a builder of culture and knowledge, and for this reason should be valued and respected. The theoretical framework is based on Mary Del Priore, Philippe Aries, Simei Andrade and Juliana Linhares. For the discussion about identity, the theoretical reference was based on the discussions of Nilma Gomes, Stuart Hall and Sheilla Zillane Almeida. The study has a qualitative approach, with a focus on ethnographic research. The method was carried out through participant observation, conversation groups and focus groups based on Bernadete Gatti's considerations. To analyze the children's speeches, the study was based on Mikhail Bakhtin's concept of dialogism and polyphony. The results of the study reveal how the children of the quilombo of Bela Aurora build their identities within their territory. The relationships established between them are formed through nature and their culture, and from there they build and affirm their identity as quilombola children, since identities are not built-in isolation, in other words, they need interaction between the sociocultural environment. Therefore, identity is not stable, it is always in constant transformation. In conclusion, the identity of the children of the quilombo of Bela Aurora is formed by means of sociocultural aspects linked to the knowledge of their ancestors, as well as the natural elements that the territory offers, such as the Gurupi River.